TO A QUESTION OF ENSURING THE SAFETY OF EDUCATION IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2019)
This article analyzes the existing problems in the education system of the Republic of Kazakhstan as a basic element of national security. An analysis of the implementation by Kazakhstan of basic agreements in the field of education and the protection of children’s rights is being conducted.The purpose of this work is to pose the problem of ensuring security in the field of education, to study the main threats in this field, to determine the subject and object of protection. When writing the work, both general theoretical and specifically scientific methods of cognition were used, namely dialectical, comparative legal, historical, formally dogmatic (specially legal), concrete legal and logical. The scientific and practical significance of the research lies in the results and conclusions.Increased scientific interest in the issue of safety of education is associated with ongoing reforms in this area, in particular, with domestic and international initiatives to improve the legal mechanism of the education system in Kazakhstan. As a result, the article concluded that there is a large complex of problems in the organization of the education system, which is still far from perfect despite the huge amount of work done in this area.The article analyzes the main stages of the creation and development of the education system in Kazakhstan, and also identifies the tasks that still face the state bodies and educational institutions of the country.The practical significance of the article lies in the possibility of using the results obtained to improve the current legislation of the Republic of Kazakhstan on the education system.Key words: education, safety, system of education.